Distribución potencial del coatí (Nasua narica) en el noreste de México: implicaciones para su conservación - Espinoza-García, Claudia R.; Martínez-Calderas, Jesús M.; Palacio-Núñez, Jorge; Hernández-SaintMartín, Anuar D. (THERYA, 2015)
Introduction: From different ecological approaches, the coati (Nasua narica) is an important procyonid. Its distribution extends from southern of the United States to Colombia. IUCN (2013) considered it as Least Concern, but in Mexico is not considered under any category of protection due to its wide distribution. Despite this, there is poor knowledge about their population status and current distribution, especially in the northeastern region of the country, where in the last 30 years there have been important changes in land use. The landscape variability that establishes the limit of physiographic subprovinces (PSP) has implications for the availability and quality of habitat for many species, and so this criterion was used. The objective of this study was to estimate the coati potential distribution in four physiographic subprovinces in Northeastern Mexico. Methodology: This study was conducted in northeastern Mexico, on the PSP: Gran Sierra Plegada (GSP), Carso Huasteco (CH); Llanuras y Lomeríos (LL) and Llanura Costera Tamaulipeca (LCT). From estimates the potential distribution was used historical and recent records and 26 predictive variables. The records were obtained from online base dates and articles, and field wok from 2006-2012. This information was analyzed with Maxent algorithm version 3.3.3k (Phillips 2013), obtaining binary maps (presence-absence) using ArcMap 9.3 (ESRI 2006). The potential distribution, as a percentage of the total area, was calculated. Results: We used 110 historical and recent records. Of these, 39 were obtained from databases and 71 fieldwork. The receiver operating characteristic (ROC) analysis showed a value of area under the curve (AUC) of 0.966 Â± 0.005. Precipitation, vegetation type, vegetation cover, altitude, slope and temperature were the most relevant variables in explaining the potential distribution model we obtained, with contribution of 70% (Table 2). The potential distribution of coati covers 19.56% of the study area. The greatest distribution areas were found in the PSPâ€™s: GSP and CH, followed by LL and LCT. Discussion and conclusions: Coati records for northeastern Mexico were found within a wide range of environmental conditions. Historical records obtained from databases are useful for the modeling of potential distribution, but it is essential to include current records (Pliscoff and Fuentes-Castillo 2011). According to ROC analysis, the model provided a good prediction. The environmental variables that explained the potential of coati distribution are similar to those mentioned in various studies as it is a species adapted to a wide range of altitude, temperature and precipitation. The PSP, GSP and CH met continuity of potential distribution. Despite this, the feasible area for the potential distribution of this species is greatly reduced, and the landscape in general was very fragmented. This fragmentation is a risk for long term viability of coati populations in Northeastern Mexico. It is proposed to establish management plans that combine agricultural production with elements that allow the distribution of this and other species, such as the planting of economic forests, as fruit orchards or timber. Key words: Adaptability, connectivity, habitat fragmentation, habitat patches, land use changes, medium-sized mammals.